Europe and Central Asia Economic Update, April 2016 : The Impact of China on Europe and Central Asia - World Bank (Washington, DC: World Bank, 2016)
The economies of Europe and Central Asia (ECA) are facing complex challenges. In the eastern part of the region the task of governments is to orchestrate a coordinated crisis response. The collapse of oil revenues and the associated decline in remittances triggered a chain reaction of shocks. Adjustment to these shocks requires a new monetary policy regime, resolution of serious fragilities in banking sectors, fiscal reforms that put government finances on a sustainable path, while guaranteeing fair burden sharing, and facilitation of job creation in sectors that compete internationally. In the western part of the region policy coordination within the European Union is being tested by the refugee crisis and a possible Brexit. Meanwhile the Chinese economy has slowed down and is in the process of fundamental transformation. Also these developments have major impacts on the ECA region. The report analyses all these challenges and points at the opportunities to become more competitive in global markets.